2002
DOI: 10.2139/ssrn.314702
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Theory of Unsecured Consumer Credit with Risk of Default

Abstract: We study, theoretically and quantitatively, the general equilibrium of an economy in which households smooth consumption by means of both a riskless asset and unsecured loans with the option to default. The default option resembles a bankruptcy filing under Chapter 7 of the U.S. Bankruptcy Code. Competitive financial intermediaries offer a menu of loan sizes and interest rates wherein each loan makes zero profits. We prove the existence of a steady-state equilibrium and characterize the circumstances under whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
464
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(485 citation statements)
references
References 18 publications
19
464
2
Order By: Relevance
“…The welfare gain is the fraction-cost-ant across time, contingencies and individuals-by which consumption in the benchmark economy would have to be scaled for the average gain to be zero. 31 This average welfare criterion is used, for example, in Chatterjee et al (2007) and is comparable to the one employed by Alvarez and Veracierto (2001). 32 In most countries, levels of both privately-negotiated and mandated severance pay increase linearly with job tenure, subject possibly to a maximum limit (see, e.g., OECD, 2013;Parsons, 2013).…”
Section: Quantitative Effects Of Severance Pay 421 Benchmark Economymentioning
confidence: 99%
“…The welfare gain is the fraction-cost-ant across time, contingencies and individuals-by which consumption in the benchmark economy would have to be scaled for the average gain to be zero. 31 This average welfare criterion is used, for example, in Chatterjee et al (2007) and is comparable to the one employed by Alvarez and Veracierto (2001). 32 In most countries, levels of both privately-negotiated and mandated severance pay increase linearly with job tenure, subject possibly to a maximum limit (see, e.g., OECD, 2013;Parsons, 2013).…”
Section: Quantitative Effects Of Severance Pay 421 Benchmark Economymentioning
confidence: 99%
“…Moreover, Livshits et al [18] find its effect on the rise of filing numbers insignificant. 9 Credit limits are reported in 1989 dollars 10 Chatterjee et al [9] provide a model with dynamic updating of creditors' beliefs about borrowers' creditworthiness that they associate with credit scores. Their paper does not, however, have anything to say about trends, which is the main point of my paper.…”
Section: Data and Motivationmentioning
confidence: 99%
“…This paper studies the implication of an improvement on the trends of the consumer credit industry. 10 Specifically, I examine how the credit limit and debt distribution as well as the number of bankruptcy filings differ in a market where creditors have information about the their borrowers' types from a credit market where they do not.…”
Section: Introductionmentioning
confidence: 99%
“…5 Attanasio, Kitao and Violante (2008) use a general equilibrium life cycle model with incomplete markets, endogenous labor decisions and medical expenditure shocks 2 Bewley (1986), Imrohoroglu (1989), Huggett (1993) and Aiyagari (1994) pioneered the literature. 3 For example, Livshits et al(2007) and Chatterjee et al(2007) suggested that medical expenditure shock is an important reason for consumer bankruptcy. Palumbo (1999), De Nardi et al(2006 and Scholz et al(2006) studied medical expenses for understanding the pattern of retirement savings.…”
mentioning
confidence: 99%